2017
DOI: 10.1055/s-0037-1607309
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Preoperative Medical Status on Microsurgical Free Flap Reconstructions: A Matched Cohort Analysis of 969 Cases

Abstract: In this study, free flap reconstruction in medically compromised patients was not associated with higher rates of revision surgeries, overall complication rates, or surgery-related costs. Complex microsurgical free flap reconstruction can therefore also be advocated in patients with high preoperative risk constellation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 34 publications
(88 reference statements)
2
11
0
1
Order By: Relevance
“…While it is widely agreed upon that smoking negatively affects free flap outcomes, a few papers showed there were no differences in complications between active smokers (AS), former smokers (FS), and nonsmokers (NS). Ehlr et al performed a retrospective analysis between AS and NS undergoing free flap reconstruction and found that there were no statistical differences in major or minor complications (Ehrl et al, 2017;Goltsman et al, 2017). Both cohorts had similar rates and types of comorbidities, and similar ASA scores.…”
Section: Discussionmentioning
confidence: 99%
“…While it is widely agreed upon that smoking negatively affects free flap outcomes, a few papers showed there were no differences in complications between active smokers (AS), former smokers (FS), and nonsmokers (NS). Ehlr et al performed a retrospective analysis between AS and NS undergoing free flap reconstruction and found that there were no statistical differences in major or minor complications (Ehrl et al, 2017;Goltsman et al, 2017). Both cohorts had similar rates and types of comorbidities, and similar ASA scores.…”
Section: Discussionmentioning
confidence: 99%
“…This technique leads to significantly improved surgical reconstruction after extensive trauma, oncological resections, and after severe infections. Moreover, in the field of oncological surgery, a more radical tumor resection can be carried out as complex and large defects may be covered by using free flaps [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. The establishment of better microsurgical equipment, surgical techniques, operative techniques, and advanced monitoring systems has led to improved flap outcome, with a flap survival as high as 95–98% [ 2 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Given the increasing cost of health services incurred by the health system, it is important to establish well-founded indications for complex surgeries, such as free flap transfer. 2 , 5 Thus, interest has grown in quantifying the measurements of quality, for example, by measuring the complication rates of medical procedures. Complications are related with increased mortality, hospitalization time, and reintervention rates.…”
Section: Introductionmentioning
confidence: 99%
“…Complications are related with increased mortality, hospitalization time, and reintervention rates. 5 …”
Section: Introductionmentioning
confidence: 99%